Evaluation of efficacy of a novel resorbable collagen membrane for root coverage of Miller's Class I and Class II recession in the maxillary anteriors and premolars - Krutika Kapare; Dharmarajan Gopalakrishnan; Rahul Kathariya; Tuhina Tyagi; Shreya Bagwe (Wolters Kluwer Medknow Publications, 2016)
Background: There are several surgical techniques in literature that have been used to perform root coverage (RC). Currently, the use of a resorbable collagen membrane (RCM) as a guided tissue regenerative material is one of the highly sought treatment modalities. The present study aimed at evaluating the clinical outcome of RC in the treatment of Miller's Class I and II recession defects in maxillary anteriors and premolars by coronally advanced flap (CAF) with and without RCM. Materials and Methods: This split-mouth study (bilateral buccal recession defects) was randomized to include 15 test (CAF + membrane) and 15 control (CAF alone) sites. Clinical parameters included gingival recession depth (RD), probing pocket depth (PPD), clinical attachment level (CAL), and keratinized tissue height (KTH) measured at baseline and 9 months postoperatively. Results: Both test and control groups showed statistically significant (P < 0.05) reductions in RD (1.54 ± 0.46 mm and 1.60 ± 0.07 mm), PPD (0.53 ± 0.15 mm and 0.94 ± 0.10 mm), increase in KTH (0.67 ± 0.90 mm and 0.73 ± 0.14 mm) and CAL (1.94 ± 0.27 mm and 2.60 ± 0.19 mm) when comparing the 9-month data from baseline. The present study showed that mean improvement in RD was 1.60 ± 0.507 and 1.53 ± 0.64 mm in both test and control groups, respectively. Mean percent RC was 58.33% ±12.19% and 56.22% ±10.22% for test and control groups, respectively. However, there were no statistically significant differences between groups for RD, PPD, KTH, and CAL. Conclusion: The results of this study suggest that both the groups CAF (control) and CAF and RCM (test) could be successfully used to treat Miller's Class I and II gingival recession defects and also demonstrated an overall significant improvement in all the assessed clinical parameters. However, there was a greater reduction of gingival RD with the use of RCM when compared with the group of CAF alone.